Growth performance of Cyprinus carpio (Linnaeus, 1758) on the basis of formulated feeds supply - Niroula, Monisha; Shrestha, Jay Narayan; Subba, Bharat Raj (Nepalese Journal of Biosciences, 2019)
Growth of fishes, a sole production of aquaculture, depends upon the physico-chemical parameters of the pond as well as quality and quantity of supplementary feed supplied. This study was carried out from 6th May to 20th June, 2017 on eight glass aquaria (47cm x 31cm x 32cm) at a rate of 25 fries per aquarium providing formulated feeds with different protein levels i.e. 25%, 30%, 35%, 40%, 45% and 50% as well as commercial feed as control. The highest and lowest body weight gain were 26.03g (diet with protein level 40%) and 15.77g (diet with protein level 25%) respectively. Similarly, the highest and lowest growth rate (g/day) and body weight gain (%) were (0.57 and 0.35) and 410.6 and 128.6) respectively. The highest mortality (28%) was seen in a diet with protein level 25% and lowest (Nil) in a diet with protein level 50%. The highest average weight gain (13.65g) was observed in first fifteen days at diet 40% protein level and lowest (4.01g) was seen in 16th to 30th days at diet with 25% protein level. There was no significance difference between average body weight gain and physico-chemical factors (pH, DO and temperature). The better growth performance of C. carpio was seen in a diet with 40% protein level. So, it is recommended for fishermen to obtain maximum production in aquaculture. Further study especially about growth in relation to formulated diet up to table size and effects of micronutrients in diet on growth performance of C. carpio is recommended for other researchers.